2004
DOI: 10.1590/s0100-879x2004000700006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclooxygenase inhibitors on gentamicin-induced nephrotoxicity in rats

Abstract: The frequent use of nonsteroidal anti-inflammatory drugs (NSAID) in combination with gentamicin poses the additional risk of nephrotoxic renal failure. Cyclooxygenase-1 (COX-1) is the main enzyme responsible for the synthesis of renal vasodilator prostaglandins, while COX-2 participates predominantly in the inflammatory process. Both are inhibited by non-selective NSAID such as indomethacin. Selective COX-2 inhibitors such as rofecoxib seem to have fewer renal side effects than non-selective inhibitors. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
(18 reference statements)
4
12
1
6
Order By: Relevance
“…Regarding the proteinuria results, it is not clear whether the benefits of treatment with the new complex come from its acting directly on kidney function or indirectly, by countering the diabetic state and thus reducing food intake, glycosuria and urinary urea. Hence, a follow-up study could involve the induction of nephrotoxicity in rats by means of drugs such as gentamycin and indometacin, followed by administration of [VO(Hdhp) 2 ] and evaluation of proteinuria [41]. Early work suggested that the vanadate ion was the prevailing form of vanadium in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the proteinuria results, it is not clear whether the benefits of treatment with the new complex come from its acting directly on kidney function or indirectly, by countering the diabetic state and thus reducing food intake, glycosuria and urinary urea. Hence, a follow-up study could involve the induction of nephrotoxicity in rats by means of drugs such as gentamycin and indometacin, followed by administration of [VO(Hdhp) 2 ] and evaluation of proteinuria [41]. Early work suggested that the vanadate ion was the prevailing form of vanadium in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Negative control group (I) were only fed and given water for 14 days, positive (II) and treatment groups (III, IV, and V) were induced by gentamycin and piroxicam for 7 days to promote inflammatory response so that the rats on each group experienced renal failure. 6 After induction, the treatment groups were given breadfruit leaves infusion by per oral and with different doses of 4.25%, 9.5%, and 19% for 7 days. After the treatments were done, the rats were fasted for 24 hours and each group were entered to a heater to dilate their veins for 5 minutes, after their tails were cut off and the blood taken into a tube and labeled for plasma creatinine measurement.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Drugs used in this study which are gentamycin and piroxicam are proven to be able to damage the kidneys for 7 days to cause renal failure. 6 Breadfruit leaves have antioxidant effects and are believed to be able to lessen renal damage because of its flavonoid contents that can decrease the creatinine levels in blood by inhibiting the activity of free radicals and lessening the damages. 7 According to assumption that breadfruit leaves contain flavonoid compounds which are anti-oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…A piora de la función renal se observó cuando la gentamicina fue asociada a un antiinflamatorio no hormonal, la indometacina. Inversamente, no se observó potencial nefrotóxico en el tratamiento gentamicina cuando asociada a rofecoxibe, un AINH selectivo de COX-2, actualmente no disponible para uso clínico (15) .…”
Section: Enfermería Globalunclassified